EFFECT OF CROP BURNING IN THE PRODUCTIVITY AND INCOME OF SUGARCANE FARMERS AT NORTHERN CEBU, PHILIPPINES. - Dr. Paulino A. Onal, Jr.; Dr. Violeta A. Neri; Virgeun M. Eraldo; Irish P. Guilaran (European Journal of Agricultural and Rural Education, 2022)
Plantation fire is very detrimental to productivity, income, and soil properties. In the Philippines, the farmers in Northern Cebu are one of the sugarcane areas that openly practice open field burning. They usually burn the cane before harvesting hence, productivity is very low as compared to the Visayan average However, statistics related to the area subjected to burning and its corresponding losses are seldom can be found. Hence, this study aims to determine the impact of cane burning in terms of losses in sugar production and the income of the farmers. An actual survey was first done last 2016 as a benchmark and every year thereafter until 2019. The GPS instrument was utilized in measuring the actual area subjected to burning. For the succeeding year, data was gathered on the actual burned area in all localities. The data gathered were encoded in the excel format template and analysis was done using the SPSS software. For the year 2019, average sugar production was “very highly productive from “less productive” for the last 3 years (2016 to 2018). The area subjected to burning was described as “very highly practiced” in 2016 reversing it to “very low practiced” in 2019. In terms of losses in sugar and income, the year 2016 was described as “very high losses” and “very low losses” in 2019. Recommended that more studies should be conducted related to this subject, in order to contribute on the pool of knowledge related to the ill effect of burning especially on the environment